P-126 Was telework during COVID-19 pandemic, suitable for everyone?. (14th March 2023) - Magroun, Imene; Aissa, Ines; Ayadi, Abir; Ayed, Wiem; Chebbi, Soumaya
Abstract : Introduction: The use of telework was strongly recommended by the World Health Organisation during the COVID-19 pandemic. It may have, in addition to advantages, psycho-social repercussions on workers. The aim of this study was to describe the psychosocial impact of telework during the era of quarantine related to the first pandemic wave of COVID-19. Materials and Methods: Descriptive cross-sectional study including Tunisian workers who teleremoted during the first health lockdown of 2020. Data was collected using a self-administered online questionnaire specifying the occupational and psychosocial characteristics of telework. Results: A total of 612 teleworkers were included. The mean age was 33±6.9 years. Sex ratio (M/F) was 0.32. Teleworking had been practiced before the health confinement by 55.6% of the cases and 86.3% had never received teleworking training. Psychosocial repercussions were noticed among 92.2%. An increase in working time was reported by 47.1%, significantly more reported by those in managerial positions (44.7%). During breaks, 48% were spending time watching TV or on social networks, which is an activity significantly correlated with sadness, chronic anxiety and sleep disorders. For benefits perceived, 85% appreciated the absence of constraints related to workplace path and 61.8% the autonomy. Telework was suitable for work according to 90.8%. Desire to continue teleworkins was expressed in 89.9%. Conclusions: The teleworking was appreciated but it had psychosocial negative repercussions. A new working mode is spreading and showing possibility to work in a different manner with similar or better results. The occupational physician will manage emergent health risk factors.